Detection of Clubroot Disease Resistance in Brassica juncea Germplasm at the Seedling Stage - Wenlong Yang; Jiangping Song; Xiaohui Zhang; Chu Xu; Jiaqi Han; Zhijie Li; Yang Wang; Huixia Jia; Haiping Wang (Agronomy, 2024)
Infection by the mustard clubroot disease pathogen Plasmodiophora brassicae has a significant negative impact on the quality and yield of Chinese mustard (Brassica juncea). At present, screening resistant resources for breeding programs is the most economical and effective method available to control this disease. In this study, we isolated P. brassicae physiological race 4 from Chinese cabbage and examined 483 mustard germplasm resources (193 leaf mustard, 96 stem mustard, and 194 root mustard) from China and abroad to identify resistance to clubroot disease at the seedling stage through irrigation inoculation with the isolated pathogen. The results showed that there were no immune varieties among the tested mustard germplasm, but that there were differences in resistance to clubroot disease among the three mustard types. More than 90% of leaf and stem mustard resources were susceptible to clubroot disease, whereas 38.66% of root mustard resources showed resistance. In total, we detected 4 highly resistant, 9 resistant, and 83 moderately resistant varieties, of which 4 highly resistant, 8 resistant, and 63 moderately resistant varieties were root mustard resources, whereas only 1 resistant and 5 moderately resistant varieties were stem mustard resources, and 15 moderately resistant varieties were leaf mustard resources. In addition, we used seven molecular markers for clubroot disease resistance in Chinese cabbage to detect stem and root mustard resources. The results showed that the marker CRk was detected in 97.87% of stem mustard and 92.49% of root mustard resources. Six markers (Crr1, Crr2, Crr3, CRa, CRb, and CRc) were detected in 18.09%, 7.45%, 2.13%, 6.38%, 12.77%, and 12.77% of stem mustard germplasms, and four markers (Crr1, Crr2, Crr3, and CRc) were detected in 8.09%, 8.67%, 10.40%, and 8.67% of root mustard germplasms, respectively, suggesting that these markers are not suitable for detecting mustard germplasm resistance to clubroot disease. This study provides a technical reference and material support for the breeding of mustard varieties resistant to clubroot disease.